Mineralogy of beach sand in Jumundo, Korea and recovery of heavy minerals using Humphreys spiral concentrator and shaking table followed by magnetic separation process. Issue 1 (4th March 2022) - Shin, Hee-Young; Chae, Soo-Chun; Yoo, Kyoungkeun
ABSTRACT: The mineralogy of beach sand, which was sampled from an island, Jumundo of South Korea, was investigated and beneficiated using gravity and magnetic separation processes. Ilmenite was determined to be a major heavy mineral and, as minor heavy minerals, zircon, monazite, and sphene were observed. Quartz, biotite, microcline, kaolinite, hornblende, and chlorite were present as gangue minerals. The Ilmenite was concentrated with a Humphrey spiral concentrator and shaking table followed by magnetic separators (drum and cross belt types). As a final product, 18% of the Humphrey spiral system concentrate was recovered, and the grade of final product was determined to be 93% ilmenite. The electron probe microscope analysis indicates that ilmenite was a solid solution of major FeTiO3, minor MgTiO3 (geikielite), and MnTiO3 (pyrophanite).